MODEL OF CREATION AND RE-ENGINEERING PRINCIPLES OF THE ECONOMIC SECURITY OF THE COMPANY - N. Unizhayev (Вестник университета)
The research allowed creating a model of economic security company. In the model, the factors influencing the process. The model has a mechanism for verifying the principle. The model has a mechanism of detail. The model knows the modern economy. Application of the model will take into account the risks. The article shows new ways of solving complex tasks. Error in the planning stage will result in serious consequences. These effects may be irreversible.